Mod Matr
Mod Matr
Matrix methods provide a very powerful tool for analyzing normal modes of coupled
oscillator systems. We'll introduce this general approach by means of an example, the
same system we discussed in detail in Section 8 of these notes. Our development will
parallel the previous treatment, but we'll use matrix language.
Example
For the system discussed in Section 8, the equations of motion (from ΣF = ma) are
mx&&1 = − ( k + k ' ) x1 + k ' x 2 ,
(1)
mx&&2 = k ' x1 − ( k + k ' ) x2 .
The equations of motion can be written as a single matrix equation:
FG m 0 IJ FG &&x IJ
1
= −
FG k + k ' −k ' IJ FG x IJ .
1
H 0 mK H &&x K2 H −k ' k + k' K Hx K
2
(2)
Each side of this equation is a column matrix. You should verify that when the matrix
products are carried out, equating the first (top) elements on the two sides gives the first
of Eqs. (1), and equating the second (bottom) elements gives the second.
We define the matrices M, K, and x as follows:
M =
FG m 0 IJ , K =
FG k + k ' − k' IJ x=
FG x IJ .
1
H 0 mK H −k ' k + k'
,
K Hx K
2
(3)
For other systems with different arrangements of masses and springs, the M and K
matrices will be different. But if the spring forces are linear functions of the coordinates,
the equations of motion can always be written in the form of Eq. (4). So the following
development is general, and is not restricted to the specific example cited above.
Note that the (1,1) element of K represents the negative of the force on mass 1 when it
is displaced a distance x 1 . The (1,2) element is the negative of the force on mass 1
when mass 2 is displaced a distance x 2 , and so on. This gives an alternative way to
determine the elements of K, instead of working out Eqs. (1) from ΣF = ma.
Caution: Some books define K with the opposite sign, so there is no minus in Eq. (4).
(See, for example, Edwards and Penney, p. 321.) We prefer to retain the minus sign, so
that Eq. (4) has the same form as the equation of motion mx&& = −kx for a single
particle.
11-2 11 Normal Modes -- Matrix Methods
General Formulation
For a normal mode, each x must vary sinusoidally, and all x's must have the same
frequency. Therefore we try to find a solution of Eq. (4) in the form
FG x IJ = C FG a IJ cosbω t + ϕg,
1 1
b g
x = Ca cos ω t + ϕ .
H x K Ha K
2 2
or (5)
This is a set of simultaneous, homogeneous equations for the elements of the column
matrix a. (This should sound familiar!) Non-trivial equations exist if, and only if, the
determinant of the system is zero, that is, when
K − λ M = 0. (8)
Thus Eq. (5) is a solution of Eq. (4) if, and only if, the value of λ = ω2 satisfies Eq. (8).
This condition is called the secular equation for the system; it is satisfied only for certain
particular values of λ, the roots of the secular equation.
For our example, we use the M and K matrices from Eqs. (3). The corresponding
secular equation is:
k + k ' − mλ − k'
= 0. (9)
−k ' k + k ' − mλ
This agrees with Eq. (4) in Section 8 of these notes (page 8-2).
Equation (8) is an algebraic equation for λ. The degree of the equation (and hence the
number of roots) is equal to the number of coordinates of the system (i.e., the number of
degrees of freedom). In some problems two or more roots may be equal.
The values of λ that satisfy Eq. (8) are called eigenvalues. There are as many values of
λ as the number of degrees of freedom of the system. For each value of λ, there is a
corresponding column matrix (or vector), giving the amplitude ratios for the x's for the
corresponding normal mode. We'll call the eigenvalues λ1 , λ2 , λ3 , L ; let a be the
column matrix corresponding to λ1 , let b be the column matrix corresponding to λ2 ,
and so on. The column matrices a, b, c, L are the eigenvectors corresponding to the
eigenvalues λ1 , λ2 , λ3 , L , respectively. Then
bK − λ Mga = 0,
1 bK − λ Mgb = 0,
2 bK − λ Mgc = 0,
3 L. (11)
b
x = C1 a cos ω1 t + ϕ1 g b
+ C2 b cos ω 2 t + ϕ 2 g b g
+ C3 c cos ω 3 t + ϕ 3 + L . (12)
x = q1 a + q2 b + q3 c + L . (14)
Now we define q to be a column matrix whose elements are the normal coordinates
q1 , q2 , q3 , L , and we define a square matrix A whose columns are the eigenvectors
a, b, c, L . For two degrees of freedom,
q=
FG q IJ
1
A=
FG a1 IJ
b1
Hq K
2
and
Ha 2 b2K. (15)
x=
FG x IJ ,
1
q=
FG q IJ ,
1
A=
FG1 1 IJ ,
Hx K
2 Hq K
2 H1 −1K
which agrees with the results at the end of Section 8 (page 8-5). (But note that there is a
lot of arbitrariness in the definition of A, because each q can be multiplied by an
arbitrary numerical constant.)
11-4 11 Normal Modes -- Matrix Methods
This whole procedure is closely related to the discussion of eigenvalues and eigenvectors
in Section 10 of these notes. Suppose we multiply both sides of Eq. (7) on the left by
M −1 . The result is
(M −1 K − λΜ
Μ −1Μ )a = 0, or (M−1 K)a = λa. (17)
If our objective is only to find the normal-mode frequencies and vibration patterns, we
are finished. Each eigenvalue λ is the square of a normal-mode frequency ω, and each
corresponding eigenvector gives the relative amplitudes of motion of the various masses
for the normal-mode motion with this frequency.
In our example problem, the matrices M, M −1 , K, and M −1 K are all symmetric, and
the eigenvectors are orthogonal. But this is an accident resulting from the symmetry of
our physical system and our choice of coordinates. In general M and K are not
symmetric; even when they are symmetric, the product M −1 K in general is not
symmetric. So in general the eigenvectors a, b, c, L are not mutually orthogonal.
But it turns out that we can develop generalized concepts of normalization and
orthogonality that are useful for fitting initial conditions and in other situations.
Normalization of Eigenvectors
a =
FG1IJ M =
FG m 0 IJ ,
H1K and
H 0 mK
the un-normalized a gives aT Ma = 2m. We multiply a by 1 2m; then aT Ma = 1.
So in our example problem, the normalized eigenvector a corresponding to the
eigenvalue λ1 = k m is
a =
1 1 FG IJ (19)
2m 1
,
HK
and the normalized eigenvector b corresponding to eigenvalue λ2 = bk + 2k 'g m is
b=
1 1 FG IJ 1 −1FG IJ
. (20)
2 m −1 H K or b=
2m 1 H K
(Note that even with the normalization conditions, the eigenvectors are not determined
uniquely; each one can always be multiplied by −1.)
Orthogonality of Eigenvectors
In the general case, if λ1 , λ2 , λ3 , L are all unequal, and if M and K are symmetric
matrices (as in our example), then it can be shown that
aTMb = 0, aTMc = 0, bTMc = 0, L . (21)
Note that the usual definition of orthogonality of two vectors a and b is aT b = 0, i.e.,
the scalar product of a and b is zero. So Eq. (21) represents a generalization of the
concepts of the scalar product and of orthogonality of two vectors. We invite you to
verify that the eigenvectors a and b in our example problem do satisfy this condition.
If the system has three or more degrees of freedom, then any two eigenvectors that
correspond to unequal eigenvalues are orthogonal in the sense of Eq. (21).
eb Kaj e j
T T
T
= λ1 bT Ma . (24)
The transpose of a product of matrices equals the product of the transposes in the reverse
order; also, (bT )T = b, so Eq. (24) can be written
11-6 11 Normal Modes -- Matrix Methods
bλ 2 g
− λ1 a T Mb = 0. (27)
Initial Conditions
We can now use the orthogonality properties of the normalized eigenvectors to work out
relations to find the constants C1 , C2 , C3 , L and ϕ1 , ϕ2 , ϕ3 , L in Eq. (12) if we
are given the initial values of the coordinates and velocities, which we denote by
x( 0) and x& ( 0) , respectively. At time t = 0, Eq. (12) becomes
Similarly, taking the time derivative of Eq. (12) and setting t = 0, we find
Now see what happens when we multiply Eq. (28) on the left by aT M. We get
The matrix product in the first term on the right is unity, because of the normalization of
the eigenvectors, and all the other matrix products on the right are zero because of
orthogonality . So Eq. (30) becomes simply
The same thing happens when we multiply Eq. (29) on the left by aT M
Now it is straightforward to solve Eqs. (31) and (33) simultaneously to obtain C1 and
ϕ1 . And all the other C's and ϕ's can be obtained the same way by multiplying Eqs.
(28) and (29) by b, c, L .
A =
FG a 1 b1 IJ
Ha 2 b2 K (for two degrees of freedom), (35)
Fa b1 c1 I
A = Ga JJ
1
GH a 2 b2
b3
c2
c3 K
(for three degrees of freedom), (36)
3
and so on. (From here on we assume two degrees of freedom; the generalization to three
or more degrees of freedom will be clear.)
FG a1 b1 IJ = MFG λ a 1 1 λ 2b1IJ
K
Ha 2 b2 K Hλ a 1 2 λ 2b2 K
. (37)
FG λ a λ b IJ = FG a b IJ FG λ
1 1 2 1 1 1 1 0IJ
Hλ a λ b K Ha b K H 0
1 2 2 2 2 2 λ2 K
. (38)
Λ=G
F λ 0 IJ .1
H0 λ K 2
(39)
Then
FG λ a
1 1 λ 2 b1 IJ = AΛ
Λ,
Hλ a
1 2 λ 2b2 K
and Eq. (37) can be written as
Λ.
KA = MAΛ (40)
11-8 11 Normal Modes -- Matrix Methods
Λ.
AT KA = ATMAΛ (41)
T
Consider the product A MA. In general, this is equal to
FG a
1 a2 IJ FG m
11 m12 IJ FG a 1 b1IJ
Hb1 b2 K Hm 21 m22 K Ha 2 b2 K
.
We see that the first row of AT and the first column of A give the normalization
condition for the eigenvector a. The first row of AT and the second column of A give
the orthogonality relation for a and b, and so on. Thus the diagonal elements of the
product AT MA are all 1, and the off-diagonal elements are all zero. That is, AT MA is
equal to the identity (unit) matrix, denoted by I.
eA MAjΛ = Λ = FGH λ0
T 1 0
λ2
IJ
K
, (42)
Thus we have the fairly astonishing result that the transformation AT MA turns M into
the identity matrix I, and it turns K into a matrix AT KA = Λ that is always diagonal,
with diagonal elements equal to the eigenvalues.
Example
a =
1 1 FG IJ b =
1FG IJ A = 1 FG1 1 IJ .
1
2m 1
,
HK H K
2m −1
,
2m H1 −1K
(44)
AT MA =
1 1FG 1 I Fm 0I 1 F1 1 I
J G J G J F1 0IJ
= G
2m 1H −1K H 0 mK 2m H 1 −1K H0 1K (45)
Fk I
1 F1 1 I F k + k ' − k ' I 1 F1 1 I
= GG m
G J G J G J
0
J . (46)
k + 2k'J
AT KA =
2m H1 −1K H − k ' k + k 'K 2m H 1 −1K GH 0 J
m K
You should verify Eqs. (45) and (46) by carrying out the matrix multiplication, both by
hand and using Maple.
11 Normal Modes -- Matrix Methods 11-9
The normal coordinate transformation is now simply x = Aq. We substitute this into the
equations of motion, Eq. (4):
Mx&& = −Kx , && = −KAq.
MAq (47)
Multiply on the left by AT :
&& = − AT KAq.
AT MAq (48)
But, as we showed above,
AT MA = I and AT KA = Λ . (49)
So Eq. (48) becomes
&& = − Λq,
FG q&& IJ
1
= −
FG λ 1 0 IJ FG q IJ
1
= −
FG λ q IJ .
1 1
q or
H q&& K
2 H0 λ2 K Hq K
2 Hλ q K
1 2
(50)
We see that the equations for the q's are decoupled; each equation contains only one q:
q&&1 = − λ1 q1 = − ω1 2 q1 , q&&2 = − λ 2 q2 = − ω 2 2 q 2 , (51)
and so forth. Each q corresponds to a single normal mode.
In our example problem, both M and K happen to be symmetric. When they are not,
our orthogonality proof is not valid, and Eqs. (26) and (27) aren't correct. When the
equations of motion are obtained from Lagrange's equations, it can be shown that M and
K are always symmetric. But when we start with ΣF = ma, the resulting matrices may
or may not be symmetric, depending on our choice of coordinates.
Suppose, for instance, that for our example system we let x 1 be the displacement of the
left mass from equilibrium and let x 2 be the elongation of the spring k '. Then the
displacement of the right mass from equilibrium is x 1 + x 2 and its acceleration is x&&1 + x&&2
You can verify that the equations of motion, in terms of these coordinates, are
mx&&1 = − kx1 + k ' x2 ,
b
x1 + &&
m && g
x2 = −kx1 − k + k ' x2 . b g (52)
In matrix form,
FG m 0 IJ FG &&x IJ = − FG k
1 −k ' IJ FG x IJ .
1
H m mK H &&x K H k
2 k + k' K Hx K 2
(53)
M=
FG m 0 IJ , K=
FG k −k ' IJ
H m mK Hk k + k'
.
K (54)
11-10 11 Normal Modes -- Matrix Methods
1 1 FG IJ 1 FG IJ F I
GH JK
1 1 1 1 3
a= b= A =
m 0
,
HK 3m −2 H K
,
m 0 −2 3
. (57)
You should check that again the operation AT MA reduces M to the identity matrix I,
and that
AT KA = Λ =
FG λ
1 0 IJ
H0 λ2
.
K (58)
You can also check the orthogonality of the eigenvectors; in this case they are not
orthogonal because M and K aren't symmetric. However, we can reformulate the
problem by adding and subtracting the equations of motion, Eqs. (52), to obtain M and
K matrices that are symmetric. Here's how we do it. We can add the two original
equations of motion, Eqs. (52), to obtain
bx1 + &&
m 2 && g
x2 = −2kx1 − kx2 . (59)
Now we take this equation and the second of Eqs. (52) to be the be the basic equations
of motion:
b g
x1 + &&
m 2 && x2 = −2kx1 − kx2 ,
mb && x g = −kx − b k + k 'g x .
(60)
x + &&
1 2 1 2
M =
FG 2m mIJ , K =
FG 2k k IJ
H m mK Hk k + k'K. (61)